Isokinetic peak torque and hamstring/quadriceps ratios in young basketball players - Gerodimos, V.; Mandou, V.; Zafeiridis, A.; Ioakimidis, P.; Stavropoulos, N.; Kellis, S. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of this study was to provide an extensive isokinetic profile, including peak torque and ''functional'' and ''conventional'' muscle group ratios, of basketball players throughout the developmental years 12-17. Furthermore, we investigated the effects of age and angular velocity on peak torque and reciprocal muscle group ratios, and observed the force-velocity pattern. Methods: Basketball players (n=180) 12 to 17 years. were divided according to their age in 6 equal (n=30) groups aged 12, 13, 14, 15, 16, 17 years. All subjects performed maximum knee extension and flexion efforts at 60o/s and 180o/s angular velocities under eccentric and concentric conditions. The absolute (Nm) peak torque was measured, and the relative peak torque (PT/BW) and ''functional'' and ''conventional'' reciprocal muscle group ratio (%) were calculated. Results: PT/BW values of knee flexors ranged from 0.98 to 2.29 Nm/kg and of extensors from 1.53 to 3.69 Nm/kg, across all age, velocity, and muscle action levels. PT/BW was higher at slow speed and during eccentric contraction irrespective of age and angular velocity/muscle action. The results indicated a significant (p<0.05) age-related increase in peak torque independent of changes in BW. The force-velocity patterns were similar across ages. The ''functional'' and ''conventional'' ratios were not affected by age, but increased with increase in angular velocity, except the CONKF/ECCKE ratio that was higher (p<0.05) at slow speed. Conclusion: The present study provides an extensive isokinetic profile of a knee joint in basketball players throughout developmental years 12-17. Coaches and physical therapist may use these information when evaluating and planning exercise programs during training and rehabilitation.